Levels of muscle activation in strength and conditioning exercises and dynamometer hiking in junior sailors - Wee, W.; Burnett, A.; Oh, W.; Lim, J.; Tan, K. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study recruited 29 (17 male and 12 female) high-level Byte class sailors aged 14-16 years to examine the average levels of muscle activation in lower limb and trunk muscles in four selected strength and conditioning exercises (leg extension, back squat and back extension exercises, a 30-second hiking hold) and a maximal three-minute hiking test (HM180). Results revealed that between-phase differences existed in the exercises examined. The level of muscle activation for the vastus lateralis for the leg extension exercise was shown to be comparable to that recorded during the back squat. Further, these exercises produced greater amounts of muscle activation when compared to those recorded during the HM180 test. Finally, the hiking hold produced greater levels of rectus abdominus activation when compared to the HM180 test.